Qalification assessment practices: new possibilities and constraints - M. N. Kicherova; M. Yu. Semenov; E. V. Zyuban (Образование и наука)
Introduction. The transformation of the educational system and the labour market determines the need for objective procedures for independent assessment of qualifications that meet the needs of all stakeholders. The need to overcome the qualification gap is becoming more acute, and it is necessary to change the configuration of connections and relationships in the process of qualifications assessment, which determines the relevance of the current research.Aim. The present publication is aimed to analyse social processes related to the development of practices for evaluating qualifications obtained in both formal and non-formal education in Russia.Methodology and research methods. The methodological framework of the research is based on the principles of the activity approach and the concept of structuration, in which the practice of qualifications assessment is viewed as a combination of social relations between individual and collective actors in the space of social and labour relations. Data collection and analysis was carried out using a qualitative methodology of the sociological approach. A semi-formal interview was selected as the method of expert survey. Twenty-four experts from various sectors of the economy (Moscow, Ekaterinburg and Tyumen) took part in the interviews.Results and scientific novelty. The possibilities and constraints of existing practices for qualifications assessment were identified: assessment centres, qualification assessment centres, internal certification, professional evaluation of working professions within the framework of the “WorldSkills” programme in Russia. The analysis of international experience is presented. Based on expert assessments, it was established that practices specific to the industrial model of the economy prevail in Russia. Thus, the infrastructure and regulatory field were established for the development of new practices of independent qualification assessment. However, the main participants of the process are not involved enough in mutual interaction. The primary sector of the economy hinders the development of the high-technology manufacturing industry and the employers who are interested in creating a competency framework. According to experts, the importance of non-formal education in the development of relevant competencies is increasing, and new mechanisms for qualifications assessment obtained in both formal and informal training are required. The authors presented the cases, which illustrate new configurations of participants’ relationships, when independent assessment of qualifications is integrated with the formal educational system at the stage of state final certification, ensuring the interrelated procedures. The article reveals the contradictions, which are manifested in the interaction between applicants/employees, employers and the state. It is concluded that such contradictions affect the institutional mechanisms for the formation of a national system of independent qualification assessment.Practical significance. The analysis of alternative models for qualifications assessment revealed the interests of different stakeholders involved in this process, the possibility of using “hybrid” forms of qualifications assessment, as well as a number of contradictions related to regulatory, functional and institutional features. The results of the study can be useful for managers of educational institutions and employers to synchronise the processes for mutual assessment of qualifications. As a result, recommendations for the development of an independent qualification assessment system in Russia are proposed, and the prospects for further research are outlined.